Need for improvements in physical pretreatment of source-separated household food waste - Bernstad, A.; Malmquist, L.; Truedsson, C.; la Cour Jansen, J. (Waste management (Elmsford), 2013)
► Increased methane yield and nutrient recovery from OFMSW can be gained through more efficient pretreatment. ► The area is currently little investigated and discussed within the scientific community. ► Pretreatment is seldom addressed in LCA of OFMSW. The aim of the present study was to investigate the efficiency in physical pretreatment processes of source-separated solid organic household waste. The investigation of seventeen Swedish full-scale pretreatment facilities, currently receiving separately collected food waste from household for subsequent anaerobic digestion, shows that problems with the quality of produced biomass and high maintenance costs are common. Four full-scale physical pretreatment plants, three using screwpress technology and one using dispergation technology, were compared in relation to resource efficiency, losses of nitrogen and potential methane production from biodegradable matter as well as the ratio of unwanted materials in produced biomass intended for wet anaerobic digestion. Refuse generated in the processes represent 13–39% of TS in incoming wet waste. The methane yield from these fractions corresponds to 14–36Nm3/ton separately collected solid organic household waste. Also, 13–32% of N-tot in incoming food waste is found in refuse. Losses of both biodegradable material and nutrients were larger in the three facilities using screwpress technology compared to the facility using dispersion technology.1Dispergator technology is a powerful milling equipment, commonly used in the paper recycling industry when recycled papers are atomizes into fibers for mixing with virgin fibers and production of new paper.1 Thus, there are large potentials for increase of both the methane yield and nutrient recovery from separately collected solid organic household waste through increased efficiency in facilities for physical pretreatment. Improved pretreatment processes could thereby increase the overall environmental benefits from anaerobic digestion as a treatment alternative for solid organic household waste.